European Investment Bank Group Activity Report 2022 Secure Europe - European Investment Bank (European Investment Bank, 2023)
Our flagship report shows how the European Investment Bank stepped up to the challenges of 2022. From our ongoing work rebuilding Ukraine's damaged towns and cities and our support for refugees, to our unwavering commitment to the global threat of climate change. The report illustrates how our backing for energy efficiency and renewable power is part of the solution to the European Union's energy security needs and its climate goals. It also shows how our support for innovation and breakthrough technologies brings tangible benefits to Europe's economic competitiveness, to its climate goals, and its strategic autonomy. The report also showcases the contribution of EIB Global, our new international development branch, to greater wellbeing around the world.